Association between Acculturation and Obesity among Female Migrants in the United Arab Emirates: A Population-Based Study - Shah, Syed M.; Paulo, Marília Silva; Loney, Tom; Nauman, Javaid; Govender, Romona D. (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Introduction Emerging evidence suggests that the “healthy migrant effect” may diminish over time with increasing years of residency in the host country. However, few studies have documented the duration of residence associated with the prevalence of obesity among female migrants. This study examined the hypothesis that acculturation is associated with an increased prevalence of obesity among female migrants in the United Arab Emirates (UAE).Results The mean ± standard deviation (SD) of the age of participants was 34.0 ± 9.9 years. The overall prevalence of overweight, obesity, and central adiposity was 30.0, 16.8, and 43.2%, respectively. The prevalence of overweight, obesity, and central adiposity varied across nationalities, with 28.6, 6.9, and 30.3% among Filipinos; 30.1, 37.5, and 66.9% among Arabs; and 33.1, 17.3, and 72.4% among South Asians, respectively. After controlling for age, female migrants with ≥5 years of residence in the UAE were twice as likely to be overweight or obese (adjusted odds ratio [aOR]: 2.12 [95%confidence interval (CI): 1.05–4.27]) and having a central adiposity (aOR: 2.05 [95%CI: 1.09–3.84]) as compared with those with fewer years of residence. Female migrants who reported walking for ≤30 min/d were less likely to be overweight or obese (aOR: 0.41 [95%CI: 0.17–0.97]) or exhibit central adiposity (aOR: 0.21 [95%CI: 0.08, 0.59]).Conclusion The findings of the study suggest that duration of residence among female migrants in the UAE is an indicator of acculturation and is associated with unfavorable changes in body composition. Public health programs should focus on promoting healthy lifestyle choices and physical activity among females in the UAE.
Keywords: acculturation; obesity; prevalence; migrants; Filipino; South Asians; Arabs